The Tripartite Nexus: Autophagy, Cancer, and Tripartite Motif-Containing Protein Family Members - Mandell, Michael A.; Saha, Bhaskar; Thompson, Todd A. (Frontiers in Pharmacology, 2020)
Autophagy is a cellular degradative process that has multiple important actions in cancer. Autophagy modulation is under consideration as a promising new approach to cancer therapy. However, complete autophagy dysregulation is likely to have substantial undesirable side effects. Thus, more targeted approaches to autophagy modulation may prove clinically beneficial. One potential avenue to achieving this goal is to focus on the actions of tripartite motif-containing protein family members (TRIMs). TRIMs have key roles in an array of cellular processes, and their dysregulation has been extensively linked to cancer risk and prognosis. As detailed here, emerging data shows that TRIMs can play important yet context-dependent roles in controlling autophagy and in the selective targeting of autophagic substrates. This review covers how the autophagy-related actions of TRIM proteins contribute to cancer and the possibility of targeting TRIM-directed autophagy in cancer therapy.